VSGA Method Based Trajectory Planning of a Novel Limb-robot - Li Liu; Han-lin Yang; Tie-feng Zhang; Ming Pang; Jie Zhao (Institute of Advanced Engineering and Science, 2013)
A new progressive genetic algorithm (PGA) was developed for trajectory planning of a novel limb-robot. The proposed trajectory planning method can be applied to get an optimal joints trajectory from the initial to the end position and orientation. On the basis of the genetic algorithm a new kind of variable structure genetic algorithm (VSGA) is proposed to solve the problem of trajectory planning of the limb-robot in complicate environments. The VSGA changes the original structure by abandoning Elitist Model, expectation selection, reproducing population and changing the probability of crossover and mutation. Experiments results show that the PGA is effective in static environments and the VSGA does well in complicate environments. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2564